Tinjauan Realisme Struktural terhadap Konsep Tiḷakkhana dalam Buddhisme Theravāda - Fattah, Galuh Nur (Media: Jurnal Filsafat dan Teologi, 2025)
This research article examines the concept of Tiḷakkhana in Theravāda Buddhism, which the researcher then referred to as Buddhist realism using structural realism as the formal object of research as well as a comparative object. The method used in writing this research article is the literature study method with the following stages: identification of research problems; literature seeking; literature evaluation; information synthesis; preparation of a theoretical or analytical framework; and writing the results of the literature study. This study found that structural realism has harmony with Buddhist realism (Ti ḷakkhana) which consists of three characteristics, namely change/impermanence (Aniccā), suffering (Dukkhā), and selflessness/absence of essence (Anattā). Although there is harmony between the two type of realism, especially in the metaphysical and epistemological aspects, there is a very contrasting difference in the ethical aspect, namely that structural realism only focuses on the metaphysical and epistemological aspects of structure as something that exists and is worthy of trust, so that the ethical aspect is completely ignored. While Buddhist realism accommodates ethical aspects that significantly influence the structure of reality, both metaphysically and epistemically. Another thing that was found is the fact that ontologically.